Conventional vs. waterjet-assisted endoscopic submucosal dissection in early gastric cancer: a randomized controlled trial - Zhou, Ping-Hong; Schumacher, Brigitte; Yao, Li-Qing; Xu, Mei-Dong; Nordmann, Thomas; Cai, Ming-Yan; Charton, Jean-Pierre; Vieth, Michael; Neuhaus, Horst (Endoscopy, 2014)
Background and study aims: A hybrid knife was recently developed to allow waterjet-assisted endoscopic submucosal dissection, which aims to speed up and simplify the procedure. This technique has been shown to be effective and safe for the treatment of early gastric cancer (EGC) but it has not yet been compared with conventional ESD.Patients and methods: In this two-center study, patients with an endoscopic and histopathological diagnosis of gastric adenoma or early gastric adenocarcinoma (meeting the extended Japanese criteria for local resection) were randomized to either conventional or waterjet-assisted ESD. The choice of knife was left to the endoscopist in the conventional group whereas the hybrid knife was used in the waterjet group. The primary end point was procedure time, and secondary outcomes included rates of en bloc resection, R0 resection, and complications.Results: A total of 117 patients (mean age 63.0 ± 10.6 years, 76 men) were randomized to either conventional ESD (n = 59; control group) or waterjet-assisted ESD (n = 58). There were no significant differences in patient demographics or lesion features between the groups. The mean procedure time was significantly shorter in the waterjet group compared with the conventional group (27.5 ± 30.6 vs. 35.0 ± 22.5 minutes; P = 0.0008), and a change of accessories was less frequently required (mean number of changes 1.4 ± 2.0 vs. 23.0 ± 15.4; P < 0.0001). There was no significant difference between the groups in the size of resected specimen, R0 resection rates, number of perforations, major delayed bleedings, or rates of complete remission of neoplasia after 3 months.Conclusions: Waterjet-assisted ESD and conventional ESD are comparably effective and safe techniques for the local treatment of EGC. The waterjet-assisted technique is a faster and simpler procedure and requires fewer accessory changes compared with conventional ESD.ClinicalTrial.gov registration: NCT01943253